2021
DOI: 10.1177/03008916211004733
|View full text |Cite
|
Sign up to set email alerts
|

Systemic effect of radiotherapy before or after nivolumab in lung cancer: an observational, retrospective, multicenter study

Abstract: Background: The combination of radiotherapy (RT) and programmed death 1 inhibitors seems to increase antitumor immune responses. Objective: To assess the outcome and the role of the best combination sequence, i.e. immunotherapy given before, during, and/or after RT, in patients with non-small cell lung cancer (NSCLC). Methods: We conducted an observational, retrospective analysis of 95 consecutive patients with advanced NSCLC who received any radiotherapy treatment and nivolumab, as clinically indicated. Media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…A non-randomised retrospective analysis of 95 consecutive patients with advanced NSCLC who received radiation therapy treatment either during or within 60 days of nivolumab showed a median overall survival (OS) of 22.4 months vs 8.6 months. 45 The definition of radiation therapy within 60 days after immunotherapy as concurrent was used because of the long half-life of nivolumab, a feature common to immune checkpoint inhibitors. A subgroup analysis of the KEYNOTE-001 trial showed that OS after pembrolizumab was significantly longer in patients who had received previous radiation therapy than in those who were radiation therapy na€ ıve (HR 0.58 P = 0.026; OS 10.7 months vs 5.3 months).…”
Section: Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…A non-randomised retrospective analysis of 95 consecutive patients with advanced NSCLC who received radiation therapy treatment either during or within 60 days of nivolumab showed a median overall survival (OS) of 22.4 months vs 8.6 months. 45 The definition of radiation therapy within 60 days after immunotherapy as concurrent was used because of the long half-life of nivolumab, a feature common to immune checkpoint inhibitors. A subgroup analysis of the KEYNOTE-001 trial showed that OS after pembrolizumab was significantly longer in patients who had received previous radiation therapy than in those who were radiation therapy na€ ıve (HR 0.58 P = 0.026; OS 10.7 months vs 5.3 months).…”
Section: Lung Cancermentioning
confidence: 99%
“…Two further retrospective studies support SITAR. A non‐randomised retrospective analysis of 95 consecutive patients with advanced NSCLC who received radiation therapy treatment either during or within 60 days of nivolumab showed a median overall survival (OS) of 22.4 months vs 8.6 months 45 . The definition of radiation therapy within 60 days after immunotherapy as concurrent was used because of the long half‐life of nivolumab, a feature common to immune checkpoint inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the findings of the PACIFIC trial, subgroup analyses revealed that patients with PD-L1-negative tumors derived the most significant benefit from incorporating RT. A retrospective study involving 95 individuals diagnosed with advanced NSCLC demonstrated that those who received nivolumab in combination with RT (including SABR, mHFRT, or CFRT) experienced a mPFS of 6.3 months and a mOS of 11.9 months [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bassanelli et al. ( 96 ) suggested that the first ≤60 days prior to the completion of RT (mOS, 22.4 months vs. 8.6 months, p = 0.005) was the most appropriate window for ICI administration. However, Bryant et al.…”
Section: Discussionmentioning
confidence: 99%